Some aspects of the development of rumen function in dairy calves reared on pasture : a thesis presented at Massey College in partial fulfilment of the requirements for the degree of Master of Agricultural Science in the Victoria University of Wellington - Stewart, John Alexander (Massey University, 1962)
Economy in feeding the ruminant is based on taking full advantage of rumen function. At birth however the rumen is not functional and the very young animal is dependent on a diet which it can digest without aid from microbial fermentation The need for a readily assimilated diet is normally fulfilled by the mothers milk. In the case of naturally reared animals this milk may continue to provide a significant proportion of the nutrients in the diet of the young animal even when rumen function has been established and it is capable of obtaining its nutrient requirements from grazing alone. Recognition of the fact that milk is an ideal food for young animals is reflected in the extended periods of milk feeding which in the past have been characteristic of the rations fed to artificially reared dairy stock. However there may be several disadvantages in such a practice, not the least of which being the amounts of milk and labour involved. In the search for more economical methods of calf rearing, the possibility of weaning at an earlier age has been investigated. Calves have been weaned as early as 3 weeks of age (Preston 1960), and it is known that calves which are provided with high quality pasture may be weaned at about 8 weeks of age without ill effect. [From Introduction]
Keywords: Rumen; Rumination; Physiology; Dairy cattle